Microplastic abundance and characteristics in the Kahayan River Downstream Area: Implications for the food safety of processed fish products - Zakiah; Muhammad Aldair Mukstofa Carda; Syahnan Aly Lubis (Acta Aquatica: Aquatic Sciences Journal, 2026)
The increasing anthropogenic activities along the Kahayan River contribute to the discharge of plastic waste into aquatic environments, leading to microplastic accumulation that contaminates river ecosystems. This study aims to analyze the abundance and characteristics of microplastics in water, sediment, and fish from the downstream area of the Kahayan River, Central Kalimantan, and to evaluate their implications for the food safety of fish-based products. Sampling was conducted at four stations within the downstream area from March to May. Water, sediment, and fish samples were processed using the wet peroxide oxidation (WPO) method, and microplastics were identified microscopically. The results revealed that microplastics were present at all sampling stations with average abundances of 3.22 particles/L in water, 7.58 particles/kg-dw in sediment, and 2.12 particles/individual in fish. No significant differences were found among stations, indicating that contamination has become widespread throughout the downstream area. Fibers were the dominant type, followed by fragments, foams, and granules, with most particles measuring <300 µm and mainly white/transparent, blue, and black/gray. These patterns suggest that microplastic sources primarily originate from domestic activities, fisheries, and insufficient waste management. The presence of microplastics in edible fish indicates potential transfer through the aquatic food chain, posing a risk to food safety and public health. Therefore, integrated mitigation measures are urgently needed, including monitoring of fish quality, setting microplastic contamination limits in food products, and strengthening plastic waste management policies to ensure the sustainability of fishery resources and public health in Central Kalimantan. Keywords: Fish; Food Safety; Microplastics; Kahayan River